HDAC8 regulates canonical Wnt pathway to promote differentiation in skeletal muscles. Issue 5 (24th September 2018) - Ferrari, Luca; Bragato, Cinzia; Brioschi, Loredana; Spreafico, Marco; Esposito, Simona; Pezzotta, Alex; Pizzetti, Fabrizio; Moreno‐Fortuny, Artal; Bellipanni, Gianfranco; Giordano, Antonio; Riva, Paola; Frabetti, Flavia; et al.
Abstract: Histone deacetylase 8 (HDAC8) is a class 1 histone deacetylase and a member of the cohesin complex. HDAC8 is expressed in smooth muscles, but its expression in skeletal muscle has not been described. We have shown for the first time that HDAC8 is expressed in human and zebrafish skeletal muscles. Using RD/12 and RD/18 rhabdomyosarcoma cells with low and high differentiation potency, respectively, we highlighted a specific correlation with HDAC8 expression and an advanced stage of muscle differentiation. We inhibited HDAC8 activity through a specific PCI‐34051 inhibitor in murine C2C12 myoblasts and zebrafish embryos, and we observed skeletal muscles differentiation impairment. We also found a positive regulation of the canonical Wnt signaling by HDAC8 that might explain muscle differentiation defects. These findings suggest a novel mechanism through which HDAC8 expression, in a specific time window of skeletal muscle development, positively regulates canonical Wnt pathway that is necessary for muscle differentiation. Abstract : In this study, we have shown for the first time that histone deacetylase 8 (HDAC8) is expressed in human and zebrafish skeletal muscles specifically in an advanced stage of muscle differentiation. The HDAC8 inhibition through a specific PCI‐34051 inhibitor in murine C2C12 myoblasts and zebrafish embryos led to skeletal muscle differentiation impairment. We also found a positive regulation of the canonical Wnt signaling by HDAC8 that might explain muscle differentiation defects.